Botticelli-style tempera portrait on tile: Imaging and specific on-site spectroscopic analysis and cleaning examination - Dal Fovo, Alice; Sepiacci, Lucrezia; Innocenti, Silvia; Striova, Jana; Fontana, Raffaella (Journal of cultural heritage, 2024)
•Comprehensive study of an alleged forgery of a tempera painting on tile with apparently Botticelli features.•Pigments identification – i.e., iron oxide pigments, cinnabar, carbon black, and calcite) - by combined FORS and Raman spectroscopy.•Pigments mapping by SCM algorithm application to the multispectral image cube.•Colorimetric analysis to quantitatively evaluate the cleaning method and provide support for an informed restoration process. In this work, a tempera painting of uncertain attribution from the Uffizi Galleries was studied. The painting, which portraits a man with apparently Botticellian features, was probably created by one of the most skilled forgers of the early 20th century, Umberto Giunti. He used a flat tile as a support, covered with preparatory layers emulating a wall painting. To shed light on the authorship of the painting, it was crucial to investigate its composing materials, as well as the execution technique and the state of conservation. To this end, non-invasive spectroscopic and imaging optical techniques were applied. Specifically, VIS-NIR multispectral reflectography was used to reveal the presence of possible preparatory drawings, pentimenti and overpaintings. Raman and Fibre Optics Reflectance Spectroscopies allowed identifying the pigments used by the artist. Finally, colour variations due to the cleaning procedure were documented in order to provide a support for an informed restoration process.